Intronização de um "Trump tropical" - Marion Aubrée (Confins)
What elements can provide an explanation for the election of former captain and MP Jair Bolsonaro? Based on the author's experience as an anthropologist working in Brazil for more than forty years on the various religious currents that inform the beliefs and opinions of the inhabitants of this country, the text highlights the successive transformations of mentalities. religious and imaginary, as well as political conjunctions explaining this unexpected result